2005
DOI: 10.1158/1055-9965.epi-04-0932
|View full text |Cite
|
Sign up to set email alerts
|

Significant Difference in the Trends of Female Breast Cancer Incidence Between Taiwanese and Caucasian Americans: Implications from Age-Period-Cohort Analysis

Abstract: Female invasive breast cancer (FIBC) in Taiwan is characterized by a striking recent increase of incidence and a relatively young median age (45-49 years) at diagnosis. The Westernization of lifestyle that is increasingly affecting younger generations of Taiwanese may have an important impact on this change. We compared epidemiologic data on FIBC in Taiwanese obtained from the Taiwan Cancer Registry with data for Caucasian Americans obtained from the database of the Surveillance, Epidemiology, and End Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
116
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 27 publications
8
116
0
Order By: Relevance
“…Asian women were about 6-18 years younger at breast cancer diagnosis than non-Hispanic whites (median age 63), and are younger than Asians (median age 56) in the United States (Yi et al, 2012). It has been suggested that the early onset of Asian women is explained by an age-period-cohort effect: the rapid change of breast cancer risk profiles allied to westernized lifestyle such as low parity, insufficient breastfeeding, and weight gain are observed among younger and more recently born women, which have resulted in a higher increase of breast cancer in the generation (Minami et al, 2004;Chia et al, 2005;Shen et al, 2005;Dhillon et al, 2011;MousaviJarrrahi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Asian women were about 6-18 years younger at breast cancer diagnosis than non-Hispanic whites (median age 63), and are younger than Asians (median age 56) in the United States (Yi et al, 2012). It has been suggested that the early onset of Asian women is explained by an age-period-cohort effect: the rapid change of breast cancer risk profiles allied to westernized lifestyle such as low parity, insufficient breastfeeding, and weight gain are observed among younger and more recently born women, which have resulted in a higher increase of breast cancer in the generation (Minami et al, 2004;Chia et al, 2005;Shen et al, 2005;Dhillon et al, 2011;MousaviJarrrahi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…According to the epidemiologic studies, prolonged exposure to estrogen, including reduced fertility rate, earlier menarche, and prolonged reproductive stimulation in the lifetimes, is significantly associated with increased risk of female breast cancer in Taiwan and in Western countries (28,29). The oxidized metabolites of estrogen, E2-3,4-semiquinones and E2-3,4-quinones, have been shown to bind to DNA to form adducts, leading to genetic damage.…”
Section: Discussionmentioning
confidence: 99%
“…First, the median age of breast cancer patients in Taiwan (45-49 years) is lesser than that in Western countries (70-74 years). 2 Second, a rise in incidence has been observed consistently in Asian countries, [2][3][4] and one age-period-cohort analysis showed that the increase in breast cancer incidence was largely due to a rise in young patients. 2 Third, a longitudinal cohort revealed that young breast cancer patients in Taiwan carried a greater risk for and shorter interval to progression to secondary contralateral primary breast cancer than in western women.…”
Section: Introductionmentioning
confidence: 97%
“…2 Second, a rise in incidence has been observed consistently in Asian countries, [2][3][4] and one age-period-cohort analysis showed that the increase in breast cancer incidence was largely due to a rise in young patients. 2 Third, a longitudinal cohort revealed that young breast cancer patients in Taiwan carried a greater risk for and shorter interval to progression to secondary contralateral primary breast cancer than in western women. 5,6 As the young age and bilateral breast cancer are more likely to be related to genetic predisposal of factors, 7,8 it is important to identify potential predisposing factors in Taiwanese patients.…”
Section: Introductionmentioning
confidence: 97%